Nutrient utilisation and carcass value of broilers fed palm kernel cake and cassava rations supplemented with ß- mannanase (2010)
An 8-week feeding trial was conducted on one 144- day old Arbor acre strain of broiler birds to investigate the nutrier utilization and carcass value of broilers fed palm kernel cake and cassava rations supplemented with ß -mannanase enzyme ir. a completely randomized design. The birds were subjected to six different dietary treatments with 24 birds per treatment ea: treatment had 3 replicates . Treatment I was the control with no test ingredients (no PKC, no Cassava grit). Treatments II, III, IV, V and VI were the test diets. In treatments II and III, maize were replaced in the diet with palm kernel cake + cassava Grit and Palm Kernel Cake +Dried Oil Cake respectively. Diet IV consisted of control + enzyme ß mannanase and diet V and VI consisted of the addition of enzyme ß mannanase to diets III & IV respectively. There was no significant difference (p>0.05, due to treatments on the weekly feed intake and body weight gain. There was no significant difference (p<0.05) on carcass value and nutrient utilization except dressed weight, eviscerated weight, neck weight expressed as percentage of dressed weight which showed significant (p<0.05) difference. Other carcass parameters evaluated did not differ significant (p>0.05). There was no significant difference in eviscerated weight and dressed weight among treatment II, VI and the control but treatment V and IV differ significantly from other treatments. There was significant (p<0.05) difference in nutrient utilization among the treatments. Treatments IV, V, and VI differ significantly from the control in dry matter digestibility, crude protein, crude fibre, ash. ether extract and nitrogen free extract. There was no significant difference in feed conversion With the noticeable trend in the result indicated that treatment V had improved performance therefore; it is more feasible to raise broilers on Cassava and palm kernel cake based diet supplemented with Enzyme mannanase for Optimum performance and productivity.